Culture & Civilization of Kaski State in the History of Nepal - Adhikari, Bam Bahadur (Rural Development Journal, 2017)
Ruled under the Lichchhavi regime in a historical period, fallen into Khasian Malla Dynasty's regime of Karnali Province in the raising period of triple power and incorporated within great Nepal Kingdom after unification of Nepal, Kaski state was most liked in the Rana regime period. Geographically being triangular shaped, decorated with snow peaks, lakes, forts-fortress, rivers and rivulets, caves-falls, bridges and interior Seti basin, Pokhara valley is also the second largest metropolitan city next to Kathmandu. Majority population of Gurung, Brahmin and Kshetri castes and Kulmandan Shah and his descents independently ruled from Kaskikot until about 318 years during 1542 to 1842 BS (1667 to 1785 AD). Successors of his dynasty ruled in Lamjung approximately 300 years since 1550 to 1842 BS (1493-1785 AD). In the medieval feudal age, war and warfare tactic was mostly discussed among the people whereas discussions and debates are mainly focused on the sectors of democracy, freedom, development and tourism development in the modern age. Kaski district is worldwide famous in the name of beautiful Pokhara Valley in the viewpoint of tourism. Pokhara Valley, situated as a second important and large city next to the Kathmandu Valley, also is zonal headquarters of Gandaki Zone consisting of 6 districts and also the Province Headquarters of No. 04 Gandaki Province. 'Pokhara Metropolitan City' is a famous and golden name of the bright star, one of the 77 districts of 14 zones of 5 development region of the country. Pokhara is also the headquarters of western development region and also the district headquarters of Kaski district. Kaski district is situated in the range of 450–7969 meters above from the sea level whereas Pokhara city remains up to 750 meter above from the sea level. The most rain falling area Lumle of Kaski district is renowned as 'Cherapunji' of Nepal. Situated in the east, Parbat district in the west, Mustang in the north and Syanja district remains in the south of Kaski district. Countless lakes, series of caves, Kumari Himal, George of Seti, Patale falls, covered by varieties of green vegetated lands and decorated by snow crown, extremely raining, multi harvestable climate, Kaski can also be regarded as a non-famine district. Despite of limitless rainfall, Kaski is famous for geographical and natural characteristics of free of flood blockade and evergreen area.